Inovasi Pembelajaran Berbasis Digital untuk Meningkatkan Motivasi Belajar Taruna Poltekpel Sumbar - taher, Muhammad Tarmizi; Alim, Akbar (Jurnal Cakrawala Bahari, 2025)
This study was the development of digital technology has brought about significant changes in the field of education, including in the field of maritime education. As an educational institution, Politeknik Pelayaran Sumatera Barat is able to adjust to digital learning innovations in order to improve the quality of the teaching and learning process. The purpose of this study is to understand how digital learning innovations can increase students' motivation to learn. The research methodology uses a deskriptif kualitatif approach using data collection techniques such as document analysis, participatory observation, and interview. The study's findings indicate that the use of interactive media, learning management system (LMS)-based instruction, and simulation-based video instruction can all increase intrinsic or extrinsic motivation. The findings of this study suggest that digital learning development is an effective strategy for raising student motivation and academic quality.